2010
DOI: 10.1002/pmic.200900488
|View full text |Cite
|
Sign up to set email alerts
|

Protein extraction from the earthworm Eisenia fetida for 2‐DE

Abstract: We identified an efficient protocol for extracting proteins from whole earthworm, Eisenia fetida, for 2-DE. Sample preparation is a critical step in a 2-DE proteome approach and is absolutely essential for obtaining good results. Six protein extraction protocols based on different protein precipitation agents were tested and evaluated using 2-DE. The methods generated remarkably different 2-DE protein spot patterns. We conclude that trichloroacetic acid (TCA)-A eliminates interfering compounds, thus allowing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In turfgrass plants, Xu et al (2008) demonstrated that TCA/ acetone method is reliable method for protein extraction for leaf tissues, while for root tissues, both TCA/acetone and phenol methods can be used. Protein extraction with TCA/acetone base is one of the frequent protocols used to extract proteins from various samples, including plants and insects (Cilia et al 2009;Wang et al 2010;Xie et al 2011;Xu et al 2008;Yin et al 2017;Zhang et al 2015Zhang et al , 2013. TCA/acetone method is an effective method to minimize degradation of protein and to eliminate interfering substances, such as salt and polyphenols (Carpentier et al 2005;Gόmez-Vidal et al 2008;Görg et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turfgrass plants, Xu et al (2008) demonstrated that TCA/ acetone method is reliable method for protein extraction for leaf tissues, while for root tissues, both TCA/acetone and phenol methods can be used. Protein extraction with TCA/acetone base is one of the frequent protocols used to extract proteins from various samples, including plants and insects (Cilia et al 2009;Wang et al 2010;Xie et al 2011;Xu et al 2008;Yin et al 2017;Zhang et al 2015Zhang et al , 2013. TCA/acetone method is an effective method to minimize degradation of protein and to eliminate interfering substances, such as salt and polyphenols (Carpentier et al 2005;Gόmez-Vidal et al 2008;Görg et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous protein extraction methods for 1-DE and 2-DE have been developed and applied for various plant samples (Alam et al 2012;Chatterjee et al 2012;Gόmez-Vidal et al 2008;Isaacson et al 2006;Rasool et al 2014;Vincent et al 2006;Xu et al 2008;Zhang et al 2015;Zheng et al 2007). Compared to the optimal methods for the extraction of plant tissues, only a few studies in the literature that compare different extraction methods for insect tissues (Cilia et al 2009;Collet & Baguñà 1993;Qin et al 2013;Wang et al 2010;Yiou et al 2013), particularly for larva and adult tissues of P. xylostella. The major drawback in proteomics research of P. xylostella is the lack of reliable protein extraction methods (Dong et al 2013;Li et al 2014a;Xie et al 2011;Yin et al 2017;Zhang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins of a large number of nematodes were extracted according to the trichloroacetic acid (TCA)-acetone procedure described previously [54]. Briefly, nematodes were ground in a mortar with liquid nitrogen until a fine white powder was produced, and then suspended with 3 mL/g fresh weight ice-cold acetone containing 10% TCA and 0.07% dithiothreitol (DTT).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were extracted according to the trichloroacetic acid‐A (TCA‐A) procedure described previously 19. Briefly, fresh whole E. fetida samples (2 g) collected from three replications were pulverized to a fine powder with liquid nitrogen and a mortar and pestle.…”
Section: Methodsmentioning
confidence: 99%